Interfacial TiN bonding of a g-C3N4/TiH1.92 type-II heterojunction photocatalyst significantly enhanced photocatalytic hydrogen evolution from water splitting. Issue 6 (18th February 2022) - Tahir, Warisha; Cheang, Tuck-Yun; Li, Jing-Han; Ling, Cong; Lu, Xiao-Jie; Ullah, Ikram; Wang, Gang; Xu, An-Wu
Abstract : An efficient interfacial TiN interaction of g-C3 N4 /TiH1.92 type-II heterojunctions photocatalyst facilitates an enhanced photocatalytic hydrogen evolution from water splitting with improved photoinduced electron-hole pairs separation and transport ability. Abstract : Graphitic carbon nitride (g-C3 N4 ), an excellent metal-free photocatalyst, is a promising candidate for overall water splitting under visible light illumination. However, some drawbacks of g-C3 N4, such as poor separation and transfer efficiency of photogenerated charge carriers, restrain its photocatalytic applications. Efficient photocatalytic water splitting could be achieved by combining g-C3 N4 with well suited divergent semiconductors to form a type-II heterojunction system. Herein, we fabricate a highly efficient type-II heterojunction system based on exfoliated titanium hydride (TiH1.92 ) nanoparticles (NPs) and g-C3 N4 nanosheets for photocatalytic water splitting. Through TiN bonding at the interface between g-C3 N4 and TiH1.92 NPs, g-C3 N4 nanosheets can be coupled with TiH1.92 NPs. Owing to their specific type-II heterostructures, strong interfacial interaction and band alignment, an efficient photocatalytic hydrogen evolution rate of 75.55 μmol h −1 is obtained, which is 4.29-fold higher than that of bare g-C3 N4 . The developed g-C3 N4 /TiH1.92 type-II heterostructures exhibit a quantum efficiency of 6.78% at λ = 420 nm. In general, this study further provides a creative route to design and develop other novel type-II heterostructured photocatalysts for efficient H2 evolution under visible light illumination.